Ion-assisted deposition of amorphous PbO layers - Semeniuk, Oleksii; Csik, A.; Kökényesi, S.; Reznik, Alla (Springer, 2017)
Lead oxide (PbO) is one of the most promising materials for application in direct conversion medical imaging X-ray detectors. Despite its high potential, conventional polycrystalline PbO layers deposited with the basic thermal evaporation method are not yet mature for practical use in X-ray imaging; indeed, they are highly porous, unstable at ambient conditions, and substoichiometric. In order to combat the above issues with PbO, we advance the basic evaporation process with simultaneous energetic ion bombardment of the growing film. We show that tuning the ion-assisted thermal deposition not only solves the structural problems of poly-PbO, but also enables the growth of a new non-crystalline polymorphic form of the material—amorphous PbO (a-PbO). In contrast to poly-PbO, novel a-PbO layers grown by ion-assisted thermal deposition are stable at ambient conditions. Structural and morphological analysis confirms that a-PbO is stoichiometric and free of detectable voids, which suggests higher bulk X-ray stopping power than porous poly-PbO.
The publisher's version of this article can be viewed at https://link.springer.com/article/10.1007/s10853-017-0998-5 A read-only accessible version of this article can be viewed with this SharedIt link at http://rdcu.be/tB19
Keywords: Lead oxide; Diagnostic imaging; X-ray imaging; Polycrystals